Transmissibility versus damage detection - Maia, Nuno M. M. (2019)
The authors thank the Portuguese Science Foundation, FCT, through IDMEC, under LAETA, project no. UID/EMS/50022/2013 and under the project UNIDEMI Pest-OE/EME/UI0667/2014.